An analysis of the arguments and counter arguments on the language of delivery of Khutbatul-Jumu‘ah (Friday sermon) in the Muslim world - Aladen, Owoyemi Samuwilu (Penerbit Universiti Kebangsaan Malaysia, 2019)
Friday sermon is seen as a veritable medium employed by Friday Imam to address various issues affecting Muslims and their communities on weekly basis. Observance of Friday prayer attracts large number of Muslim worshippers who listen to sermon that precedes the prayer. However, there have been arguments and counter arguments on the view of some Muslim jurists that Arabic language should be the appropriate language of the delivery of the Friday sermon. Adopting analytical method, the paper aims at examining the divergent opinions of the Muslims’ jurists on the language of Friday sermon. The finding of this study reveals that there are arguments and counter arguments on the language of delivery of Friday sermon due to the fact that there is no Quran verse or authentic hadith that specifically makes delivery of Friday sermon in Arabic compulsory. The finding also shows that Khutbatul- Jumu‘ah (Friday sermon) cannot be equated with Salat (ritual prayer) and for the Friday sermon to have positive impact on the life of the congregation, Friday Imam is expected to deliver his sermon in the language understood by the majority of the congregation.